Oral History Program Interview: Vera Ruth Woodall Criswell - Criswell, Vera Ruth Woodall
Born in Seymour, Baylor County, Texas on July 23, 1909, Criswell moved between Texas, Oklahoma, Arizona, and California through the 1920s and 1930s. Her fascinating interview compares many aspects regarding Southern California, California's Central Valley, and Arizona. Though she arrived in Visalia in 1937, her many experiences before and after include employer relations with migrants, racial minority relations, discrimination at school, farm mechanization, New Deal policies, dust storms, labor and government camps, problems for women in camps, California border checks, women and children working in fields, health and nutrition, why organizing strikes failed, welfare abusers, what the term "Okie" meant, and the many errors in The Grapes of Wrath.